Development of Comics Based on the Local Wisdom North Sumatra Culture in the Mathematics Subject Geometry Material in Elementary School - Indah Ayu Kartika; Nila Lestari (Journal of Education and Teaching Learning, 2024)
This research addresses the inadequacy of existing teaching materials in elementary school mathematics, particularly in Medan, Indonesia, by proposing the development of a Comic-Based Local Wisdom of North Sumatra Media for Geometry Learning in Grade 5. Current materials lack a focus on local wisdom and fail to align with the diverse cultural context. The research utilizes a modified 5D model, involving (1) Define, (2) Design, (3) Development, (4) Effectiveness Testing, and (5) Dissemination. The study emphasizes the importance of incorporating local traditions and cultural elements into teaching materials to enhance students' interest and understanding. The comic-based media integrates geometry concepts with North Sumatran culture, offering an alternative and engaging learning tool. The validation process involves content experts, media experts, and learning experts, all of whom declare the developed media highly suitable for instructional use. The locally-based wisdom comic media proves effective in making the learning process more engaging and facilitating students' comprehension, contributing to the improvement of mathematics education in elementary schools.